Reseach on the Application of Pixel Art in Game Character Design - Zufri, Tubagus; Ardani, Nurul Aqmarina (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
This paper analyses the trend, design fundamentals, and design principles of contemporary character design from digital game. It discusses that even though the design styles of today’s digital art era are flourishing with diverse thinking and visual approach, the classic pixel art style will never go out of style. The fundamental element of artistic design in pixel art style is a single element, a pixel. Many designers prefer using the single pixel style as the fundamental element of their artistic design, which has led to the creation of various intriguing design categories. Despite the prevalent use of full high-definition 3D rendering images in contemporary digital game design, the pixelated style remains a timeless tribute to the classics with an enduring impact, given its promising development prospects. Pixelated design is now being applied to practice by more designers and artists, and it has gradually become a unique form of artistic visual expression.